Is the middle cranial fossa a reliable predictor of temporal lobe volume in extant and fossil anthropoids?. Issue 4 (1st April 2020) - Pearson, Alannah; Polly, P. David; Bruner, Emiliano
Abstract: Objectives: We investigate the suitability of middle cranial fossa (MCF) size as a proxy for temporal lobe volume (TLV), examining the strength of the association between TLV and MCF metrics and assess the reliability predicting TLV in fossil anthropoids. The temporal lobe of the primate brain is a multimodal association cortex involved in long‐term memory, auditory, and visual processing with unique specializations in modern humans for language comprehension. The MCF is the bony counterpart for the temporal lobe providing inferences for fossil hominin temporal lobe evolution. We now investigate whether the MCF is a suitable proxy for the temporal lobe. Methods: A sample of 23 anthropoid species ( n = 232, including 13 fossil species) from computed tomography (CT) scans of ex vivo crania and magnetic resonance imaging (MRI) of the in vivo brain were generated into three‐dimensional (3D) virtual models. Seven linear metrics were digitally measured on the right MCF with right TLV calculated from in vivo MRI. Results: Regression analyses produced statistically significant correlations between TLV and all MCF metrics ( r ≥ 0.85; p ≤ 0.0009) with TLV predictions within ±1 standard error and three MCF metrics (posterior‐width, mid‐length, and mid‐width) the most reliable predictors of TLV with only one metric weakly associated with TLV. Discussion: These findings indicate a strong association between the MCF and TLV, provide reliable predictors of fossil TLV that were previously unattainable, allow the inclusion of fragmentary fossil material, and enable inferences into the emergence of modern human temporal lobe morphology.